2018
DOI: 10.3171/2017.7.jns171286
|View full text |Cite
|
Sign up to set email alerts
|

Combination ipilimumab and radiosurgery for brain metastases: tumor, edema, and adverse radiation effects

Abstract: OBJECTIVE Tumor and edema volume changes of brain metastases after stereotactic radiosurgery (SRS) and ipilimumab are not well described, and there is concern regarding the safety of combination treatment. The authors evaluated tumor, edema, and adverse radiation-induced changes after SRS with and without ipilimumab and identified associated risk factors. METHODS This single-institution retrospective study included 72 patients with melanoma brain metastases treated consecutively with upfront SRS from 2006 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
(33 reference statements)
2
41
1
Order By: Relevance
“…This result suggests that GKRS is a safe irradiation procedure for brain metastases from malignant melanomas, which is consistent with past reports of SRS for brain metastases [42]. However, the outcomes obtained in this series also showed that combining SRS with immune checkpoint inhibitors significantly increased the incidence of radiation injury, which supports results obtained in several prior studies [1,17,18,30,31,34,43,44]. We hypothesized that this observation might be attributable to the increased radiosensitivity of brain tumors, leading to subacute inflammatory changes and lymphocyte toxicity, as described in recent reports focusing on the novel systemic agents [1,17,18,31,32,35].…”
Section: Discussionsupporting
confidence: 83%
“…This result suggests that GKRS is a safe irradiation procedure for brain metastases from malignant melanomas, which is consistent with past reports of SRS for brain metastases [42]. However, the outcomes obtained in this series also showed that combining SRS with immune checkpoint inhibitors significantly increased the incidence of radiation injury, which supports results obtained in several prior studies [1,17,18,30,31,34,43,44]. We hypothesized that this observation might be attributable to the increased radiosensitivity of brain tumors, leading to subacute inflammatory changes and lymphocyte toxicity, as described in recent reports focusing on the novel systemic agents [1,17,18,31,32,35].…”
Section: Discussionsupporting
confidence: 83%
“…Melanoma is a common skin cancer caused by hyperproliferation of abnormal melanocytes. It typically occurs in the skin, but, although rarely, also in the mouth, intestines, brain or eyes [1][2][3]. It is extremely aggressivet and accounts for a large proportion of death among skin tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, OS was significantly shorter in the non-concurrent treatment group at just 8 months compared to 19.1 months for the concurrent therapy cohort ( 84 ). Many trials, including those done by Diao et al ( 98 ), Anderson et al ( 82 ) and Yusuf et al ( 88 ), have also used “4 weeks or 1 month” as the threshold value to describe “concurrent therapy”. In these trials, patients treated with combined ICIs and SRS experienced better results than those diagnosed with non-concurrent therapy ( 79 , 82 , 90 , 98 ).…”
Section: Establishing the Best Performing Sequence And Schedule Of Inmentioning
confidence: 99%
“…Many trials, including those done by Diao et al ( 98 ), Anderson et al ( 82 ) and Yusuf et al ( 88 ), have also used “4 weeks or 1 month” as the threshold value to describe “concurrent therapy”. In these trials, patients treated with combined ICIs and SRS experienced better results than those diagnosed with non-concurrent therapy ( 79 , 82 , 90 , 98 ). In the study carried out by An et al , they suggested that “5.5 months” could also be used to describe “concurrent therapy” as a threshold value ( 83 ).…”
Section: Establishing the Best Performing Sequence And Schedule Of Inmentioning
confidence: 99%